Pengaruh Kompetensi dan Kegiatan Komite Audit terhadap Kualitas Audit - Dayu Swispa Pamantau (Jurnal Kajian Akuntansi dan Auditing, 2019)
The accuracy of the determination of policies within a company is determined by the quality of the resulting audit by the auditor. Audit quality will be higher when the auditor assigned to have high competence in the field of audit, in addition to the quality of the audit will be better if the activities of the audit committee to provide oversight of internal party activities. Therefore, this study purpose to determine the effect of the competence and activities of the audit committee on audit quality. The study was conducted at the KAP region of the city of Padang and Pekanbaru. The sample used was 43 respondents. The analysis method used is to use multiple linear regression models. Based on the results of hypothesis testing results found that the competence and activities of the audit committee have a significant effect on audit quality auditors working in KAP of Padang and Pekanbaru city.